2013
DOI: 10.1371/journal.pone.0064519
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of Respiration in Rat Lines Selectively Bred for High or Low Anxiety

Abstract: In humans, there is unequivocal evidence of an association between anxiety states and altered respiratory function. Despite this, the link between anxiety and respiration has been poorly evaluated in experimental animals. The primary objective of the present study was to investigate the hypothesis that genetic lines of rats that differ largely in their anxiety level would display matching alterations in respiration. To reach this goal, respiration was recorded in high-anxiety behavior (HAB, n = 10) and low-anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 40 publications
6
47
1
Order By: Relevance
“…Clinical studies have shown that panic disorder, characterized by acute and unexpected anxiety attacks and substantial anxiety over the possibility of experiencing further attacks, is associated with symptoms including palpitations, shortness of breath, sweating, and hyperventilation (1). In addition, high levels of anxiety-related behavior in rats are associated with elevation of the resting respiratory rate (9). The respiratory rate also decreases during certain specific responses to stress, for instance during freezing behavior in the rat, when it is associated with ultrasonic vocalizations (19).…”
mentioning
confidence: 99%
“…Clinical studies have shown that panic disorder, characterized by acute and unexpected anxiety attacks and substantial anxiety over the possibility of experiencing further attacks, is associated with symptoms including palpitations, shortness of breath, sweating, and hyperventilation (1). In addition, high levels of anxiety-related behavior in rats are associated with elevation of the resting respiratory rate (9). The respiratory rate also decreases during certain specific responses to stress, for instance during freezing behavior in the rat, when it is associated with ultrasonic vocalizations (19).…”
mentioning
confidence: 99%
“…These responses are likely linked with animals' anxiety state, as they are sensitive to anxiolytic drug diazepam (23) and are significantly increased in rats with induced high-anxiety behavior (32). There are also substantial differences in respiratory pattern between rats bred for low-anxiety behavior compared with animals bred for high-anxiety behavior (5). The brains substrate of the anxiety-related respiratory responses is poorly understood.…”
mentioning
confidence: 99%
“…(and bradycardia) response in LAB compared to HAB and NAB is due to an increased sensitivity in the vestibular-thermoregulatory/cardiovascular pathways that are psychogenetically selected by the elevated plus-maze test. Previous studies [5,6] have identified phenotypic differences in the cardio-respiratory control in LAB compared to HAB/NAB animals, and this study identifies a novel unpredicted phenotypic difference. In addition, it is also possible that selection of the LAB phenotype included selection for animals with enhanced vestibular sensitivity.…”
Section: Do Our Findings Challenge the Validity Of The "Hypothermia Nmentioning
confidence: 63%
“…other physiological parameter such as an increased hypothalamic expression and release of vasopressin [32], differences in pain sensitivity [22], increased hormonal response of the HPA axis to novelty [26] and elevated frequency of breathing [5] in HAB rats.…”
Section: Accepted Manuscriptmentioning
confidence: 99%